2010
DOI: 10.1002/lapl.201010097
|View full text |Cite
|
Sign up to set email alerts
|

Diode-pumped CW frequency-doubled Nd:CNGG-BiBO blue laser at 468 nm

Abstract: Efficient and compact blue laser output at 468 nm is generated by intracavity frequency doubling of a continuouswave (CW) diode‐pumped Nd:CNGG laser at 935 nm. With 17.8 W of diode pump power and the frequency‐doubling crystal BiB3O6 (BiBO), a maximum output power of 490 mW in the blue spectral range at 468 nm has been achieved, corresponding to an optical‐to‐optical conversion efficiency of 2.8%; the output power stability over 4 h is better than 2.6%. To the best of our knowledge, this is first work on intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
5
1
Order By: Relevance
“…4a, in which two wavelengths laser emission could be found with centers at 933.0 and 936.8 nm, respectively. This was different from that obtained with Nd:GGG, Nd:GAGG, Nd:CNGG, and Nd:CLNGG crystals, where only one emission was observed for CW operation [19][20][21][22]. It was further found that the two wavelength lasers had almost the same thresholds and were all unpolarized.…”
Section: Resultscontrasting
confidence: 69%
“…4a, in which two wavelengths laser emission could be found with centers at 933.0 and 936.8 nm, respectively. This was different from that obtained with Nd:GGG, Nd:GAGG, Nd:CNGG, and Nd:CLNGG crystals, where only one emission was observed for CW operation [19][20][21][22]. It was further found that the two wavelength lasers had almost the same thresholds and were all unpolarized.…”
Section: Resultscontrasting
confidence: 69%
“…The other way is to develop lasers emitting at the lowest wavelength possible in the near infrared [2] and to perform nonlinear conversion. Various solid lasers in blue spectra range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] have been obtained by nonlinear conversion of the transi tion of solid lasers [18][19][20][21][22][23][24][25][26][27]. These blue lasers are effi cient and powerful, nevertheless their wavelengths are too high compared to the 442 nm He-Cd laser.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, diode-pumped solidstate laser systems have been established as an efficient and compact light source for these applications. By frequency doubling the radiation from Nd 3+ lasers, one can generate blue, green, and red radiation, and by implementing the technique of intracavity doubling, one can achieve high conversion efficiencies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Secondary optical fre-quency references based on visible lasers locked on iodine hyperfine absorption lines have made a real breakthrough with the development of frequency doubled diode-pumped Nd 3+ lasers at 532 nm [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%